Analysis of Well Kick Countermeasures with Concurrent Method in MFA Well of NKL Field - Muh Fatwa Asmawat; Aprilino Alfa Kurmasela; Abdul Gafar Karim; Fatma; Bambang Wicaksono; Sepryanto Fernandus D; Darmiyati, Iin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2021)
The goal is to drill an MFA well down to 4593 feet (MD) in the NKL field. At a depth of 4593 feet, the MFA well had a well kick problem as a result of drilling into the high pressure formation zone while gas was present in the formation. Gas bubbles in the soil are a sign that the MFA well has kicked. Correct handling of this well kick issue is necessary to avoid blowout. Well kick countermeasures on the MFA well in the NKL field are evaluated using the concurrent method, which includes collecting data from drilling implementation reports, analyzing new mud (kill mud) weight, maximum allowable mud weight (maximum allowable mud weight), pump, and formation pressure calculations when a well kick occurs. Make an evaluation by comparing the results of the calculation with the implementation data from the field, and then make inferences. The evaluation of the well kick countermeasures' implementation using the concurrent approach revealed that the kill mud weight was 12.21 ppg. The muck had to be moved using 2208 pump strokes and 36.79 minutes of pumping time. When the mud pump is stopped and the SIDP price is zero, there is no flow in the annulus, indicating that the well kick has been managed well. The most effective method for developing well-thought-out countermeasures is the concurrent strategy.